2016
DOI: 10.3389/fpls.2016.00314
|View full text |Cite
|
Sign up to set email alerts
|

454-Pyrosequencing Reveals Variable Fungal Diversity Across Farming Systems

Abstract: Oasis farming system is common in some parts of the world, especially in the Arabian Peninsula and several African countries. In Oman, the farming system in the majority of farms follows a semi-oasis farming (SOF) system, which is characterized by growing multiple crops mainly for home consumption, but also for local market. This study was conducted to investigate fungal diversity using pyrosequencing approach in soils from a farm utilizing a SOF system which is cultivated with date palms, acid limes and cucum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…The results of physicochemical analysis indicated that KH and MA soils are loamy sand, whereas WT soil is sandy loam. Loamy sand soils are commonly used for growing several crops, including tomatoes and cucumbers (Kazeeroni and Al-Sadi, 2016). Soil pH is an important consideration for farmers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of physicochemical analysis indicated that KH and MA soils are loamy sand, whereas WT soil is sandy loam. Loamy sand soils are commonly used for growing several crops, including tomatoes and cucumbers (Kazeeroni and Al-Sadi, 2016). Soil pH is an important consideration for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of electrical conductivity (EC) and pH were as explained by Zhang et al (2005). Total nitrogen was analyzed using Kjeltec Analyser (FOSS TECATOR, Sweden) (Kazeeroni and Al-Sadi, 2016). Potassium (K), sodium (Na) and calcium (Ca) contents were analyzed with flame photometric method (Sheerwood 450 flame photometer).…”
Section: Physicochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Dates palm ( Phoenix dactylifera L.) is one of the oldest and most important fruit trees in the Middle East [1, 2]. The total worldwide production of dates is around 7.2 million tons, with approximately 5.1 million tons produced by countries in the Middle East [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the development in molecular techniques, several DNA-based approaches were developed which enabled the detection of several fungal species that are either difficult to grow on synthetic media, or those which are slow growing and usually outgrown by fast growing species. These include the use of pyrosequencing or MiSeq sequencing which made the detection and identification of fungal and bacterial species easy, not only from plant and food material but also from environmental samples such as water and soil [1, 1115]. …”
Section: Introductionmentioning
confidence: 99%